Anaconda - Llosa, Luis; Lopez, Jennifer 1970-; Ice Cube (Musician); Voight, Jon 1938-; Stoltz, Eric; Columbia Pictures (Culver City, CA Columbia TriStar Home Video, 1997)
A group of documentary makers in the rainforest are terrorized by a giant anaconda snake, which an insane snake expert wants to capture.
Originally released as motion picture.
Director of photography, Bill Butler; production designer, Kirk M. Petruccelli; editor, Leander T. Sales; music, Randy Edelman.
Jennifer Lopez, Ice Cube, Jon Voight, Eric Stoltz.
Rated PG-13.
DVD.
English, French or Spanish dialogue, French or Spanish subtitles; closed-captioned.
Keywords: Anaconda -- Drama; Snake hunting -- Amazon River Region -- Drama; Motion pictures -- Production and direction -- Drama; Motion pictures -- Production and direction; Drama; Feature films; Horror films; Video recordings for the hearing impaired